2021
DOI: 10.1101/2021.10.26.465853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inefficient exploitation of accessory receptors reduces the sensitivity of chimeric antigen receptors

Abstract: Chimeric antigen receptors (CARs) can re-direct T cells to target abnormal cells but their activity is limited by a profound defect in antigen sensitivity, the source of which remains unclear. Here, we show that CARs have a >100-fold lower antigen sensitivity compared to the TCR when antigen is presented on antigen-presenting-cells, but nearly identical sensitivity when antigen is presented as purified protein in isolation. Given that the TCR uses other, accessory, receptors to achieve high sensitivity, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
(193 reference statements)
2
3
0
Order By: Relevance
“…S26). This could be consistently rationalized by an improvement in the dissociation rate (table S4), in accordance with kinetic proofreading models for TCR activation (25)(26)(27)(28)(29)(30). The differences observed were not a result of pMHC complex stability (fig.…”
Section: Molecular Mimicry Of the Phox2b Antigen Elicits 10lh Cross-r...supporting
confidence: 80%
See 1 more Smart Citation
“…S26). This could be consistently rationalized by an improvement in the dissociation rate (table S4), in accordance with kinetic proofreading models for TCR activation (25)(26)(27)(28)(29)(30). The differences observed were not a result of pMHC complex stability (fig.…”
Section: Molecular Mimicry Of the Phox2b Antigen Elicits 10lh Cross-r...supporting
confidence: 80%
“…In an analogous manner to TCRs, both antigen density and pHLA dissociation rate from the 10LH CAR can contribute to our observation that HLA-A*23:01, which has approximately two orders of magnitude reduced binding to 10LH relative to HLA-A*24:02 (2.6 μM versus 11 nM K D ), shows potent CAR T cell killing of tumor cells (14), because both interactions show similar k d values by SPR (0.0085 s −1 versus 0.0022 s −1 ). These results allow us to establish a relationship between pHLA dissociation rate from the scFvexpressed as CAR dwell time-and CAR T cell activation, cytokine release, and cytotoxicity, established by previous studies focusing on both TCRs and CARs (28)(29)(30).…”
Section: Peptide Backbone Plasticity Enables High-affinity Complex Fo...supporting
confidence: 53%
“…It is well established that engagement of the T‐cell adhesion receptors CD2 (which binds CD58) and LFA‐1 (which binds ICAM‐1) improve the sensitivity of T cells to antigens (Huse, 2017 ; Siller‐Farfán & Dushek, 2018 ; Zhu et al , 2019 ; preprint: Burton et al , 2021 ). Recently, we reported that this improvement in sensitivity was progressively lost as the antigen affinity was lowered and consequently, engagement of these receptors increased the ability of T cells to discriminate antigens (Pettmann et al , 2021 ) but the mechanism remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that engagement of the T cell adhesion receptors CD2 (which binds CD58) and LFA-1 (which binds ICAM-1) improve the sensitivity of T cells to antigens (9, 18, 23, 36). Recently, we reported that this improvement in sensitivity was progressively lost as the antigen affinity was lowered and consequently, engagement of these receptors increased the ability of T cells to discriminate antigens (4) but the mechanism remains unclear.…”
Section: Resultsmentioning
confidence: 99%